India, Preparation for the world of work : education system and school to work transition - Pilz, Matthias [Herausgeber] (Springer VS, 2016)
"This book explores how the Indian education and training system prepares young people for the world of work and for the requirements of the employment market - because India is a leading industrialised nation with a very young population and a high demand for a skilled workforce. Indian experts write from a course-specific perspective, offering a comprehensive picture of educational policy, curriculum design and cultural characteristics. The virtual absence of a formalised system of vocational training in India underlines the importance of this research." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.3.4 Asien; Bildungssystem; Sekundarbereich; Berufsbildung; Hochschulbildung; Informelles Lernen; Indien